Candidate exclusion regulations under Inter-American Law - Albán González, Javier (2022)
This article studies the approach of Inter-American Law and the Inter-American Court of Human Rights to the limitations on the right to run for popularly elected positions, with special emphasis on the regulations of Peruvian Electoral Law on the exclusion of candidates. The article proposes an interpretation that allows the practice of the States to reach a consensus with the text of Article 23 of the American Convention, which at first sight seem incompatible, offering a legal theory that allows to overcome what the authors consider to be a situation of relative unpredictability.